Immune checkpoint blockers plus chemotherapy as the first-line treatment for advanced or metastatic squamous non-small-cell lung carcinoma: a network meta-analysis and economic evaluation - Lang, Yitian; Yang, Jie; Cao, Weican (Frontiers in Pharmacology, 2025)
ObjectiveImmune checkpoint inhibitors (ICIs) combined with chemotherapy have shown significant survival benefits in advanced squamous non-small-cell lung cancer (NSCLC), as confirmed by clinical guidelines. However, the high cost of ICIs imposes a substantial economic burden on patients. An economic evaluation of various ICIs plus chemotherapy regimens is urgently needed. This study assessed the cost-effectiveness of several regimens for advanced squamous NSCLC from the perspective of the Chinese healthcare system.MethodsA network meta-analysis (NMA) was conducted to compare the efficacy of different ICIs plus chemotherapy regimens. The key outcomes, including hazard ratios for overall survival (OS) and progression-free survival (PFS), were extracted from clinical trials. A cost–utility analysis was performed.ResultsData from six clinical trials involving 2,548 patients were analyzed. The camrelizumab plus chemotherapy and penpulimab plus chemotherapy regimens showed the greatest OS benefit, while camrelizumab plus chemotherapy provided the best PFS benefit. The tislelizumab plus chemotherapy regimen incurred the lowest treatment cost (42,882.3), with an incremental cost–utility ratio (ICUR) of 4,062.0 per quality-adjusted life-year (QALY). The camrelizumab plus chemotherapy regimen offered the highest survival benefit (2.344 QALYs), with an ICUR of 6,078.4/QALY. In addition, the ICUR of the penpulimab plus chemotherapy regimen is 25,712.3/QALY. The ICURs of three other ICI plus chemotherapy regimens were higher than the willingness-to-pay threshold.ConclusionAmong the six ICI plus chemotherapy regimens evaluated, tislelizumab plus chemotherapy demonstrated the lowest ICUR, followed by the camrelizumab plus chemotherapy regimen. However, with a threshold of 13,445/QALY or 40,334/QALY, camrelizumab plus chemotherapy provided greater QALY benefits than tislelizumab plus chemotherapy. Thus, camrelizumab plus chemotherapy is recommended as the preferred first-line treatment for advanced squamous non-small-cell lung cancer in this context.